Designing frames: The use of precedents in parliamentary debate. (January 2018) - Umney, Darren; Lloyd, Peter
Abstract : Using the naturally-occurring data of official UK Parliamentary transcripts for the development of a new high speed rail project, this paper takes one characteristic of the design process, the use of precedent, to explore how problems and solutions are framed during discussion. In contrast to accounts of reframing that describe one big insight changing the design process we show how one particular precedent allows a series of attempts at reframing to take place in discussion. We conclude by arguing that precedents enable a diffusion of semi-objective meaning in discussion, similar to a prototype in a more conventional design process. This contrasts with other types of discourse elements, such as storytelling, that function through the subjective accumulation of meaning. Highlights: Legislative processes should be considered as processes of design. One precedent can lead to a series of different re-framings. Precedents reconfigure networks of actors through parliamentary discourse. The use of precedent is an element of discourse comparable to storytelling. Precedent tagging could be carried out using computational approaches.